Chemical Surface Modification of Polymeric Biomaterials for Biomedical Applications - Sun, Wei; Liu, Wenying; Wu, Zhaoqiang; Chen, Hong (Macromolecular rapid communications., 2020)
This review focuses on the attachment of polymer brushes to polymeric biomaterial substrates by chemical surface modification methods for biomedical applications. In the first part of this paper, a general introduction to the synthesis of polymer brushes is given. Thereafter, a comprehensive overview of recent work on the chemical surface modification of polymeric biomaterials, with a focus on “grafting‐to,” “grafting‐from,” and “grafting‐through” strategies, is provided. Finally, some representative cutting‐edge biomedical applications of modified polymeric biomaterials, mainly including antifouling materials and biocompatible materials, are highlighted. On the basis of this literature study, a perspective on future trends in this field is provided. A comprehensive overview of recent work on chemical surface modification of polymeric biomaterials, with a focus on grafting‐to, grafting‐from, and grafting‐through strategies, is provided. Furthermore, some representative cutting‐edge biomedical applications of modified polymeric biomaterials, mainly including antifouling materials and biocompatible materials, are highlighted.